LITTER DECOMPOSITION RATES IN RANGELANDS AND THEIR IMPACT ON PLANT PHYSIOLOGICAL CHARACTERISTICS - Khushbekova Muhayyo Sobirjon qizi; Oxunova Surayyo Sobirjonovna; Abdumuratova Dinora Akmal qizi; Djurabayeva Farannoz Oybekovna; Ravshanov Xudoyberdi Ravshanovich (TADQIQOTLAR, 2026)
Abstract The degradation of rangelands is widely recognised as a significant global issue. It is crucial to assess the resilience of rangeland ecosystems by evaluating decomposition rates and plant ecophysiological responses. This study used a Tea Bag Index (TBI) methodology to assess soil decomposition, as well as enzymology techniques to determine chlorophyll content. The findings showed that soil decomposition rates increased with distance from watering wells. However, a contrasting trend was observed in the change in chlorophyll a content of Artemisia diffusa. In conclusion, further investigation is required across the entire rangeland area.